2015
DOI: 10.1021/ed500850c
|View full text |Cite
|
Sign up to set email alerts
|

Diels–Alder Reaction Using a Solar Irradiation Heat Source Designed for Undergraduate Organic Chemistry Laboratories

Abstract: Recently proposed solar reflectors developed from satellite dishes have the ability to be incorporated into student laboratory procedures to eliminate electricity use while demonstrating green chemistry techniques at the same time.There have been recent attempts to make chemical synthesis procedures more environmentally friendly. As a result, demand to incorporate more green chemistry techniques into student laboratories has increased. Electricity use is one area of environmental concern because fossil fuels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…As long as the solar irradiation levels were 500 W/m 2 or greater, the location, time and day did not seem to affect the results of the solar reactions. Similar results for reactions were obtained during all seasonal periods throughout various times of the day [9][10][11][12].…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…As long as the solar irradiation levels were 500 W/m 2 or greater, the location, time and day did not seem to affect the results of the solar reactions. Similar results for reactions were obtained during all seasonal periods throughout various times of the day [9][10][11][12].…”
Section: Resultssupporting
confidence: 81%
“…Recently, it was shown that solar energy could be used to perform high temperature chemical reaction as the heat source [9][10][11][12]. A solar reflector was designed out of satellite dishes and Mylar ® tape, and a Friedel-Crafts acylation reaction was performed using the solar reflector as the sole thermal heat source.…”
Section: Introductionmentioning
confidence: 99%
“…Self‐healing composites have previously been developed by embedding healing agents (ie, reactive chemicals and catalysts) into the matrix using microcapsules that release the healing agent upon crack damage 6‐8 . In recent years, intrinsic repair has been achieved through reactions between specific molecular structures, in particular, via the Diels‐Alder (DA) reaction 9 . The DA reaction is widely used in the construction of intelligent polymer materials because of its high efficiency and multi‐functionality 10‐19 .…”
Section: Introductionmentioning
confidence: 99%
“…Diels-Alder cycloaddition reactions are widely used in synthetic organic chemistry since it was first described by Otto Diels and Kurt Alder in 1928 [7,8]. Due to its interesting mechanism and accessibility to upper-level undergraduate coursework, there have been a variety of reports which involve Diels-Alder reaction in undergraduate laboratory classes [9][10][11][12]. The challenges of effective teaching the Diels-Alder reaction, however, stem from understanding the three-dimensional perspective of the molecules and molecular orbitals in an adduct formation which most undergraduate students have poorly understood in class.…”
Section: Introductionmentioning
confidence: 99%
“…Due to complexity including prediction of regioselectivity, stereochemistry and reactive positions, these concepts tend to be one of the most challenging sections to comprehend for undergraduate students. Such complexity becomes more pronounced when students deal with polycyclic aromatic hydrocarbons such as anthracene which is a well-known diene in undergraduate laboratory classes [12]. In this manuscript the integration of web-based computational aids with the hands-on synthetic experiment and its effectiveness in facilitating students' understanding will be discussed.…”
Section: Introductionmentioning
confidence: 99%